PERSEPSI GURU DAN ORANG TUA TENTANG PENGARUH MAKANAN HALAL TERHADAP PERILAKU ANAK USIA DINI - alawiah, tutialawiah (Hamka Ilmu Pendidikan Islam, 2025)
Halal food is not only seen as a religious obligation, but it is also believed to influence the development of behavior in early childhood. This study aims to describe the perceptions of teachers and parents regarding the impact of halal food on the behavior of young children. The research used a descriptive qualitative method with teachers and parents of children at Early Childhood Education (PAUD) institutions as the research subjects. Data collection techniques were carried out through interviews, observations, and documentation. Data analysis was carried out through stages of data reduction, data presentation, and drawing conclusions. The results of the study show that teachers and parents have a positive perception of providing halal food, which is believed to affect children's behavior such as emotional calmness, compliance with rules, as well as habituation of moral and religious values from an early age. The conclusion of this study emphasizes the importance of synergy between schools and families in providing halal food as part of character education for early childhood.